RETRACTED: Post-acute (long) COVID-19 quality of life: validation of the German version of (PAC19QoL) instrument - Srikanth Umakanthan; Mariam Monice; Salona Mehboob; Cheryl Linda Jones; Sam Lawrence (Frontiers Media S.A., 2023)
PurposeThe aim of our study was to validate a German translation of the post-acute (long) COVID-19 quality of life (PAC-19QoL) instrument among German patients with long COVID-19 syndrome.Patients and methodsThe PAC-19QoL instrument was translated into the German language and administrated to patients with long COVID-19 syndrome. Cronbach's alpha coefficient was used to analyze the internal consistency of the instrument. Construction validity was evaluated by using Pearson's correlation coefficient and Spearman's rank correlation. Scores of patients and controls were compared using the Mann-Whitney U-test.ResultsA total of 45 asymptomatic and 41 symptomatic participants were included. In total, 41 patients with long COVID-19 syndrome completed the PAC-19QoL and EQ-5D-5L questionnaires. PAC-19QoL domain scores were significantly different between symptomatic and asymptomatic participants. All items achieved a Cronbach's alpha >0.7. There was a significant correlation between all domains on the test (p < 0.001), with the highest correlation between total (r = 0.994) and domain 1 (r = 0.991). Spearman's rank correlation analysis confirmed that the instrument items correlated with the objective PAC-19QoL examination findings.ConclusionThe German version of the instrument is valid and reliable and can be a suitable tool for research and daily clinical practice among patients with long COVID-19 syndrome.